Comparison of Glasgow Admission Prediction Score and Amb Score in predicting need for inpatient care. Issue 4 (14th February 2018) - Cameron, Allan; Jones, Dominic; Logan, Eilidh; O'Keeffe, Colin A; Mason, Suzanne M; Lowe, David J
Abstract : Aim: We compared the abilities of two established clinical scores to predict emergency department (ED) disposition: the Glasgow Admission Prediction Score (GAPS) and the Ambulatory Score (Ambs). Methods: The scores were compared in a prospective, multicentre cohort study. We recruited consecutive patients attending ED triage at two UK sites: Northern General Hospital in Sheffield and Glasgow Royal Infirmary, between February and May 2016. Each had a GAPS and Ambs calculated at the time of triage, with the triage nurses and treating clinicians blinded to the scores. Patients were followed up to hospital discharge. The ability of the scores to discriminate discharge from ED and from hospital at 12 and 48 hours after arrival was compared using the area under the curve (AUC) of their receiving-operator characteristics (ROC). Results: 1424 triage attendances were suitable for analysis during the study period, of which 567 (39.8%) were admitted. The AUC for predicting admission was significantly higher for GAPS at 0.807 (95% CI 0.785 to 0.830), compared with 0.743 (95% CI 0.717 to 0.769) for Ambs, P<0.00001. Similar results were seen when comparing ability to predict hospital stay of >12 hour and >48 hour. GAPS was also more accurate as a binary test, correctly predicting 1057 outcomes compared with 1004 for Ambs (74.2vs70.5%, P=0.012). Conclusion: The GAPS is a significantly better predictor of need for hospital admission than Ambs in an unselected ED population.